SOLUSI MENGATASI HAMBATAN KOMUNIKASI BERAGAMA DI DAERAH MAYORITAS KARO - Mirandha W. Lubis, Mhd Rifai Luthfi (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2021)
Abstract: Indonesia is known as a diversity of tribes, ethnicities and religions proving that Indonesia is a pluralistic society. This can be a very pluralistic potential, with various nuances of real pluralism in various ethnic groups with specific backgrounds: regional languages, traditions, customs, arts, culture and religion. Seeing the reality of a pluralistic Indonesian nation and the importance of inter-religious dialogue being carried out, the authors, using the research method of library research, took the theme of writing: "Solutions for Overcoming Barriers to Religious Communication in Karo-majority areas". The results of the study show that there are obstacles in inter-religious dialogue. The obstacles are that dialogue is still carried out in limited groups, not militant, internal conflict, lack of supporting institutions, prejudice, injustice, historical experience and lack of openness. Concrete steps to overcoming obstacles are living together (live in) with dialogue partners, educating people to be able to manage conflict, taking sides with humanity, involving all elements of society, no truth claims, building cooperation, strong and militant commitments, and strengthening dialogue forums between religions. Keywords: Communication, between religious communities, obstacles, and how to overcome them. Abstrak: Indonesia dikenal sebagai keanekaragaman suku, etnis dan agama membuktikan bahwa Indonesia merupakan masyarakat majemuk. Hal tersebut dapat menjadi potensi yang sangat pluralistik, dengan berbagai nuansa kemajemukan yang nyata dalam berbagai kelompok etnis dengan kekhasan latar belakang: bahasa daerah, tradisi, adat istiadat, seni, budaya dan agama. Melihat realitas bangsa Indonesia yang majemuk dan pentingnya dialog antar umat beragama dilakukan, maka penulis, dengan metode penelitian studi kepustakaan, mengambil tema tulisan: “Solusi Mengatasi Hambatan komunikasi beragama didaerah mayoritas karo”. Hasil penelitian menunjukkan bahwa ada hambatan dalam dialog antar umat beragama. Hambatan itu adalah dialog masih dijalankan pada kelompok terbatas, tidak militan, konflik internal, kurang lembaga penunjang, prasangka, ketidakadilan, pengalaman sejarah dan kurangnya keterbukaan. Langkah konkret mengatasi hambatan adalah tinggal bersama (live in) dengan partner dialog, mendidik masyarakat agar bisa mengelola konflik, berpihak pada kemanusiaan, melibatkan semua elemen masyarakat, tidak ada klaim kebenaran, membangun kerja sama, komitmen yang kuat dan militan, serta memperkuat forum dialog antar umat beragama. Kata Kunci: Komunikasi, antar umat beragama, hambatan, dan cara mengatasi.